Medical engagement and improving quality of care - Spurgeon, Peter (Future Hosp J, 2015)
This paper argues that establishment of a positive culture that promotes and enhances levels of medical engagement should be a key objective of medical leadership. Two particular and critical arguments underlie this proposition a) that levels of medical engagement, as measured by the Medical Engagement Scale, is strongly associated with organisational performance, including quality of care; and b) that any aspiration to achieve an organisational culture known as ‘clinically led’ cannot be achieved without high levels of medical engagement. Medical engagement as a concept is discussed, as well as the need for robust and reliable assessment. Approaches to support organisations enhance levels of engagement are presented as part of the goal to improve overall care quality.